Molecular Investigation of Some Beta-lactamase Genes by PCR and DNA Sequencing Techniques in clinical Escherichia coli - AL-Lami, Rana AH; Al-Hayanni, Huda S. A.; Shehab, Zina Hashem (Iraqi Journal of Science, 2022)
In this study, out of 50 isolates of some nosocomial infections from some Baghdad hospitals, only 13 (26%) were identified as Escherichia coli. Depending on selective media, morphological and biochemical tests the species was then confirmed by molecular methods. Later on  antimicrobial resistance test was performed by the Kirby-Bauer method. The molecular characterization of blaTEM and blaCTX-M genes in different clinical isolates of E. coli was done through polymerase chain reaction (PCR) by utilizing special primers. These genes were positive to only 4 (30.7%) isolates. The sequence of nucleotides of positive genes was carried out for four isolates. The results showed that there was no variance in the nucleotide sequence between Iraqi isolates compared with the global isolates, and that they were 100% identical to many genera of Enterobacteriaceae. Finally, due to the indiscriminate use of antibiotics, these genes in human strains were likely the source of widespread drug resistance.